2022
DOI: 10.1142/s1363919622500207
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Drivers of Radical and Incremental Innovation Performance: The Role of a Firm’s Knowledge-Based Capital and Organisational Agility

Abstract: Organisational agility, a specific dynamic capability, constitutes a key success factor in today’s dynamic business environments. However, it is unclear whether and how firms’ knowledge-based capital enables organisational agility. Moreover, mechanisms through which organisational agility translates knowledge-based capital into innovation performance are poorly understood. This study fills these gaps by investigating direct effects of knowledge-based capital (i.e., human, social, and organisational capital) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 134 publications
0
2
0
Order By: Relevance
“…Eisele et al (2022) reinforce the idea that knowledge capabilities (such as those provided by business intelligence) can foster agility, subsequently influencing innovation and overall performance. fect on performance through agility.…”
supporting
confidence: 59%
“…Eisele et al (2022) reinforce the idea that knowledge capabilities (such as those provided by business intelligence) can foster agility, subsequently influencing innovation and overall performance. fect on performance through agility.…”
supporting
confidence: 59%
“…In other words, timely access to information allows organizations to generate new ideas and overcome complex problems for developing radically new products and services. The findings of Eisele et al (2022) also revealed that knowledge-based human is positively related to incremental innovation because it enables firms to quickly reconfigure processes related to the design of incrementally new products and services. Despite substantial progress made in the current literature to explain for the significant influences of KHRM practices on innovation, the precise mechanisms underlying the relationship between KHRM practices and specific forms of innovation such as radical and incremental innovation remain poorly understood.…”
Section: The Impact Of Knowledge-based Hrm Practices On Innovation Co...mentioning
confidence: 96%
“…Regarding the influence of KHRM practices on radical and incremental innovation, Eisele et al (2022) indicated that radical innovations generally involve higher levels of uncertainty and complexity than incremental innovations. To address these complexities, organizations need to rely on knowledge-based human to develop capabilities that provide timely access to knowledge and information, which is particularly important during the design phase of radical innovations.…”
Section: The Impact Of Knowledge-based Hrm Practices On Innovation Co...mentioning
confidence: 99%